PELATIHAN PEMBUATAN AKUN KIP-K 2024 BAGI SISWA SMK DI PESAWARAN LAMPUNG - Lusia Septia Eka Esti Rahayu; Anisa Martiah; Heditia Umi Ismulyani; Muhamad Rasid; Subhi; Marlia Sari (STIE Muhammadiyah Kalianda, 2024)
Obstacles faced by students include a socio-economic background from the lower middle class, low interest in continuing their education, and a lack of understanding of the KIP-K registration procedure. To overcome this, the proposed solution is to carry out activities to provide accurate information, provide motivation, and provide assistance during the KIP-K Program registration process. The aim of this activity is to provide guidance or assistance so that relevant information regarding tuition funding assistance solutions from the KIP-K Program can be conveyed effectively, stimulate interest in continuing education to a higher level, and increase the understanding and skills of the target audience. The method used in this activity is clinical coaching. This program was successfully participated in by class XII students of SMK Ma'arif 3 Pesawaran Lampung. The results show a positive impact by increasing understanding of information knowledge regarding KIP-K by 100%, the level of understanding regarding KIP-K is 87.5%. the level of understanding regarding creating a KIP-K account is 83.3%, the level of knowledge regarding the requirements for creating a KIP-K account is 83.3%.